GARAP KENDHANGAN INGGAH LAMBANGSARI: YOGYAKARTA, SURAKARTA, DAN NARTOSABDAN - Harun Ismail; Leny Nur Ekasari; Sri Eko Widodo (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
This research describes the variations of kendhangan (drumming) techniques in the inggah of Gendhing Lambangsari, which can be presented in three distinct styles: Yogyakarta, Surakarta, and Nartosabdan. The focus of the problem in this article lies in how the drumming patterns of the three styles are presented in the Lambangsari gendhing and what the characteristics of the musical taste of each style are.The study employs a descriptive-analytical qualitative method, utilizing literature review, field observations, and in-depth interviews with karawitan masters (empu). Data analysis was conducted by deconstructing technical aspects based on the concept of garap, supported by musical parameters such as laya (tempo), irama (rhythm), and pematut (appropriateness).The results indicate clear aesthetic distinctions within each style: (1) the Yogyakarta style tends to evoke an antal (steady) and lugas (straightforward); (2) the Surakarta style tends to convey a prenes (flirtatious) and kenes (charming); and (3) the Nartosabdan style tends to project a gumyak (cheerful) and gobyok (lively). These findings confirm that integrating these three styles into a single performance not only enriches the musical presentation but also enhances the aesthetic value and appeal of the karawitan performance.